Allogenic hematopoietic stem cell transplantation in two siblings with adult metachromatic leukodystrophy and a systematic literature review. Issue 1 (6th May 2021) - Videbæk, Cecilie; Stokholm, Jette; Sengeløv, Henrik; Fjeldborg, Lone U.; Larsen, Vibeke Andrée; Krarup, Christian; Nielsen, Jørgen E.; Grønborg, Sabine
Abstract: Two siblings were diagnosed with adult metachromatic leukodystrophy (MLD) and treated with hematopoietic stem cell transplantation (HSCT). While the older sibling was symptomatic at the time of diagnosis, her younger brother was diagnosed and transplanted at the presymptomatic state. We describe patients' clinical, biochemical, and genetic features, as well as neuropsychological and neurophysiological test results, and brain magnetic resonance imaging from pretransplantation and posttransplantation assessments. Both patients converted to complete donor chimerism and arylsulfatase A levels normalized 3 months posttransplantation. Twelve months posttransplantation, neurological and neuropsychological assessment for both patients showed stabilization, and they remained stable for the 38 months long observation period. To assess the effect of HSCT used as treatment for the rare, adult MLD subtype on survival and stabilization, we performed a systematic literature review and included 7 studies with a total of 26 cases. Of these 26 cases, 6 patients died of HSCT‐related complications and 2 patients had graft rejection. Of the remaining 18 patients, 2 patients improved after HSCT, 13 patients stabilized, and 3 patients progressed, suggesting that HSCT potentially benefits adult MLD patients. Larger studies focusing on this subtype are needed and recommendations on criteria for HSCT in adult MLD need to be evolved.